Creativity in Higher Education: the Case of Portugal VS. Lithuania - Amorim, Vanessa; Bernardes, Óscar; Santos, Bárbara; Rua, Orlando Lima (E- Revista de Estudos Interculturais, 2021)
This study was intended to evaluate the creativity perception in the context of higher education by analyzing its different sub-components: - activities during classes; - students’ involvement during the classes; - evaluation of the degree of creativity in the classroom; and - the creativity understanding. The researchers designed a questionnaire to understand the different insights of students related to creativity. The study was focused on two target groups: - 1 st: students from Vilnius University of Applied Sciences - Group 2: students from Porto Accounting and Business School. For a better analysis and evaluation of the results obtained in the questionnaire, the Lewis Model was used to understand in which cultural categories the countries under study would be inserted and its impact on creativity. The statistical analysis results demonstrate that Lithuanian students show higher average results in the different sub-components of perceived creativity in higher education. However, the results indicate that the view of the concept understanding is close between Portuguese and Lithuanian students. The research that is presented in this paper is the first research related to creativity in education comparing Portugal and Lithuania and it could be a good base for further research of two economically similar yet culturally different countries